Religious Moderation Attitude: Development Scale - Rena Latifa; Muhamad Fahri; Naufal Fadhil Mahida (Universitas Islam Tribakti Lirboyo Kediri, 2022)
The assessment of religious moderation is still in its early stages of development and is having difficulty accepting the criteria indicated. As a result, religious moderation is sometimes interpreted as being indecisive, only making judgments that favor certain people or groups, and seeming irresponsible by refusing to take a political stance. Furthermore, the concept of religious moderation is frequently misunderstood. Using the CFA validity test approach, this study attempts to create a religious moderation instrument based on a psychological paradigm in which an attitude is understood based on particular ideas (beliefs), emotions, and prior behavior toward religious moderation (Confirmatory Factor Analysis). We define religious moderation as the middle way or not being extreme in one view (tawassuth), upholding balance and justice (i'tidal), appreciation of life's diversity (tasamuh), relying on consensus-based problem-solving (Shura), engaging in constructive good deeds for the common good (ishlah), is active and innovative in leading goodness (qudwah), and can accommodate the state, nation, and culture (muwwathanah). The study's findings reveal three (3) aspects of religious moderation, represented by characteristics such as particular ideas (beliefs), emotions, and prior experiences connected to the principles of religious moderation discussed above.